(untitled) (Texas Journal of Engineering and Technology, 2022)
This article examines the process that takes place in adjusters for the heating process. The synthesis of the adjuster for the heating process using the Matlab program was analyzed in model mode. In the course of the study, characteristic values were obtained based on the transmission functions in the system. The results were obtained through a block diagram to optimize the adjustment parameters of the adjuster.